2018
DOI: 10.1021/acs.jpcc.7b11059
|View full text |Cite
|
Sign up to set email alerts
|

Role of Gold Adatoms in the Adsorption of Sulfide Species on the Gold(001)-hex Surface

Abstract: We have studied the adsorption of reduced sulfur species on the Au(001)-hex surface from diluted ethanolic sulfide solutions by STM, XPS, electrochemical techniques and DFT calculations. Our results reveal the absence of S multilayers because all S species are bonded to Au surface atoms. Monomeric S adsorbs at hollow sites forming a (2×2) lattice, while S 2 species either capture the gold adatoms (Au ad) that result from the hex lifting or remove Au ad from the substrate forming well-ordered S 8-like structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…These results, and those recently reported by our group [24], allow a deeper understanding of the sulfur-gold chemistry in 2D systems. Indeed, adsorbates include monomeric sulfur, monomeric sulfur-gold complexes, adsorbed disulfides and disulfide-gold complexes, and the substrate plays a significant role in the adsorbate geometry.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…These results, and those recently reported by our group [24], allow a deeper understanding of the sulfur-gold chemistry in 2D systems. Indeed, adsorbates include monomeric sulfur, monomeric sulfur-gold complexes, adsorbed disulfides and disulfide-gold complexes, and the substrate plays a significant role in the adsorbate geometry.…”
Section: Resultssupporting
confidence: 83%
“…Similar quasi-rectangular polysulfide structures have been observed on the Au(001) surface, and the basic building blocks have been also assigned to S 2 species [23]. However, there are new evidences indicating that the disulfide species are stabilized by gold atoms forming well ordered disulfide-gold complexes [24].…”
Section: Introductionsupporting
confidence: 59%
“…Secondly, on the terraces the herringbone reconstruction is completely lifted after the H2S exposure [33][34][35] . We attribute the protrusions to Au adatoms originating from the lifting of the herringbone, which are decorated with S to form S-Au complex 30,[36][37][38][39][40] . The STM images were acquired at 100 K. Even at this temperature, some of the S-Au are slightly mobile (circles in Fig.…”
mentioning
confidence: 99%
“…55 While for the Au(001) surface S can still deploy Au adatoms in sulfur−metal complexes, it seems that this is not always true for thiol molecules. 58,59 In fact, it was shown that the bridging thiolate motif (−RS−) is more preferred than the staple motif for the Au(001) surface. 3 When the hex reconstruction is lifted, generally monolayerhigh Au islands form, covered by a continuous molecular phase.…”
Section: ■ Introductionmentioning
confidence: 99%